Legal and contemporary issues on covid-19 in Nigeria (2021)
The effect of the Covid-19 pandemic outbreak on the legal landscape in Nigeria is diverse and multifaceted. Its effect has gone way beyond every conceivable outcome and has affected not only the health of the individuals in any given community and the health sector, but movement, travel, social interactions. businesses, and the day-lo-day lives of the Nigerian people. Adopting the sociological jurisprudence school of legal theory which recognizes the relationship betwixt and among law. society. technology. and accepted social culture, this paper charts the effect of Covid-19 on identified Segments of the legal landscape and the society viz: health. labor. tourism, criminal law. And procedure. family law. as presented by legal scholars in various legal subfields. A holistic approach lo resolving the legal issues brought about by covid-19 is recommended as the best foot forward such as; respecting the basic human rights of citizens would ensure that the vulnerable can access medical care: health data accumulated based on die pandemic is managed wise/y (and no! subject lo3abtise): defaulters of Covid-19 regulations are handled in a manner that reflects respect for die rule of law and due process: medical waste management is handled in such a way that it does not affect the community and result in die spread of disease, inter alia.